The use of rituximab in myasthenia gravis and Lambert–Eaton myasthenic syndrome. Issue 6 (14th April 2010) - Maddison, Paul; McConville, John; Farrugia, Maria Elena; Davies, Nicholas; Rose, Michael; Norwood, Fiona; Jungbluth, Heinz; Robb, Stephanie; Hilton-Jones, David
Abstract : Aim: To assess the treatment effects of rituximab in a population of patients with myasthenia gravis and Lambert–Eaton myasthenic syndrome. Methods: Data on all treated patients in the UK were collected from referring physicians, with full case ascertainment and follow-up. Results: Since 2004, 10 patients with generalised myasthenia gravis (three of whom were positive for muscle-specific tyrosine kinase (MuSK) antibodies) and two patients with Lambert–Eaton myasthenic syndrome (LEMS) were treated with rituximab. Using the Myasthenia Gravis Foundation America postintervention status, three patients (25%) achieved remission, and a further five (42%) improved clinically over an 18-month period. Only one patient developed worsening symptoms. The probability of achieving remission was unrelated to the duration of neurological symptoms prior to treatment. All LEMS and MuSK antibody patients improved following rituximab treatment. Conclusion: In a relatively large, unselected group of patients with myasthenia gravis and LEMS, rituximab treatment resulted in a significant clinical improvement in two-thirds of cases. As a selective, B cell targeted therapy, rituximab should be considered as a treatment option for patients with either myasthenia gravis or LEMS for whom standard immunosuppressive treatments have been unsuccessful.